Julia Margaret Cameron photographs to electrify you with delight and startle the world ; [accompanies the exhibition ... Art Gallery of New South Wales, Sydney, 13 August 2015 - 25 October 2015 ; Victoria and Albert Museum, London, 28 November 2015 - 21 February 2016] - Cameron, Julia Margaret 1815-1879 (Mack, 2015)
Julia Margaret Cameron (1815-79) was one of the most important and innovative photographers of the 19th century. Criticized in her lifetime for her unconventional techniques, she is now celebrated as a pioneering portraitist. 2015 marks the bicentenary of Camerons birth and the 150th anniversary of her first museum exhibition the only one in her lifetime held at the Victoria and Albert Museum in 1865. Drawing on the V&As significant collection, which includes photographs acquired directly from Cameron and letters she wrote to the museums founding director, Curator Marta Weiss tells the story of Camerons artistic development. She also presents, for the first time, a group of photographs recently revealed to have belonged to Camerons friend and mentor the artist G.F. Watts. This discovery sheds light on previously unacknowledged aspects of Camerons experimental approach